2023
DOI: 10.36877/pmmb.a0000324
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics: Comprehensive Exploration of the Growth Promotion Mechanisms in Shrimps

Abstract: As feed accounts for a significant proportion of a farm’s expenditure, animal nutrition is one of the key profit determinants. Attributed to the size-dependent market value, enhancing shrimps' growth is essential to maximize profit. Despite not being the best option, antibiotics are often used as growth-promoting agents in farming. Although this trend is less explicit in aquaculture, increasing production yield is paramount, especially when intensive aquafarming compromises animal growth and increases disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 429 publications
0
7
0
Order By: Relevance
“…The use of probiotics in shrimp culture has been shown to modulate the gut microbiome, leading to improved growth and health. Studies found that probiotics can enhance shrimp performance and stimulate beneficial bacteria in the gut ( Servin Arce et al, 2021 ; Xuan Hui Goh et al, 2023 ). Studies emphasized the potential of gut microbiome manipulation in aquaculture, including the use of probiotics ( Holt et al, 2021 ).…”
Section: Modulation Of the Gut Microbiomementioning
confidence: 99%
See 4 more Smart Citations
“…The use of probiotics in shrimp culture has been shown to modulate the gut microbiome, leading to improved growth and health. Studies found that probiotics can enhance shrimp performance and stimulate beneficial bacteria in the gut ( Servin Arce et al, 2021 ; Xuan Hui Goh et al, 2023 ). Studies emphasized the potential of gut microbiome manipulation in aquaculture, including the use of probiotics ( Holt et al, 2021 ).…”
Section: Modulation Of the Gut Microbiomementioning
confidence: 99%
“…Probiotics have been shown to enhance the structural integrity of the hepatopancreas and gut, hence facilitating the animal's digestion and absorption of nutrients. Improving gastrointestinal health was crucial for ensuring the well-being of animals, fostering their development, and providing protection against opportunistic diseases (Xuan Hui Goh et al, 2023 ).…”
Section: Modifying Gastrointestinal Morphologymentioning
confidence: 99%
See 3 more Smart Citations